2009
DOI: 10.1515/text.2009.008
|View full text |Cite
|
Sign up to set email alerts
|

A study of interruption in Chinese criminal courtroom discourse

Abstract: This article is based on a corpus of transcripts of four criminal courtroom trials in China. It investigates interruption in the Chinese criminal courtroom discourse as a highly institutionalized and strongly goal-oriented discourse. The study focuses on the number, functions, causes, and distribution of interruptions as well as their correlation with the Chinese legal system and legal culture. Interruptions in Chinese courtroom trials are substantially asymmetrical in terms of the number, functions, and cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Gao (2012) described varying signals of yielding the floor. Ulijn and Li (1995), Li (1999Li ( , 2001 and Liao (2009) presented interruptions in different discourses. Liu (2004) and Kuang (2005) teased out the varieties of interruptions in Chinese.…”
Section: Understanding Extended Concurrent Speech From Different Persmentioning
confidence: 95%
“…Gao (2012) described varying signals of yielding the floor. Ulijn and Li (1995), Li (1999Li ( , 2001 and Liao (2009) presented interruptions in different discourses. Liu (2004) and Kuang (2005) teased out the varieties of interruptions in Chinese.…”
Section: Understanding Extended Concurrent Speech From Different Persmentioning
confidence: 95%
“…The definitions of interruption have been approached both from sequential (Beattie, 1982;Ferguson, 1977;Liao 2009;Schegloff, 2000) and interactional perspectives (Coon & Schwanenflugel, 1996;Goldberg, 1990;Hutchby, 1992;). In this instance, due to the institutional power entitled to the first host, it is by default that the turn floor is under the control of the first host, and any attempt to prevent her from talking is regarded as interruption.…”
Section: Methodsmentioning
confidence: 99%
“…In doctor-patient exchanges, "physicians use more non-supportive interruptions than patients; patients failed to interrupt physicians more frequently than vice versa, even more so with senior physicians than with doctors-in-training" (Menz & Al-Roubaie, 2008, p. 645). As is the same case in the criminal courtroom, Liao (2009) investigated the number, functions, causes, and distribution of interruption in a Chinese criminal courtroom and found that prosecutors interrupt the most often, the defence lawyers the least, while the defendant is the most frequently interrupted party.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overlap has been referred to as a ‘control device’ (West & Zimmerman 1977:527) because speakers who succeed in usurping the current speaker's turn-at-talk may develop their own topics and take the reins of an interaction (see e.g. Bogoch & Danet 1984; Carbó 1992; Ainsworth-Vaughn 1995; Li, Krysko, Desroches, & Deagle 2004; Liao 2009). While overlap is often ‘competitive’ (Schegloff 2000), it may also serve a supportive or affiliative function, conveying involvement and helping interactants to build camaraderie (see e.g.…”
Section: A General and Linguistic Account Of The Us Senate Intelligenmentioning
confidence: 99%